Implementasi Ekonomi Pertahanan Indonesia Melalui Sektor Anggaran Pertahanan - Seftiana, Ledy; Guntur Eko Saputro; Suwito Suwito (CV. AFDIFAL MAJU BERKAH, 2024)
The implementation of military spending through the Indonesian defense industry has shown gradual positive development, driven by efforts to establish an independent defense sector. This study examines the role of Indonesia's defense budget in supporting national security and fostering economic growth, focusing on the collaboration between state-owned enterprises (BUMN) and private companies (BUMS). The defense budget is applied progressively to balance the country's limited resources and the relatively low level of external threats. Using a qualitative research method, this study analyzes data from relevant literature, reports, and policies to evaluate the impact of the defense budget on the Indonesian economy. The research explores key aspects such as the gradual development of defense equipment, the role of research and development (R&D) in driving innovation, and the partnership between public and private sectors to strengthen the local defense industry. The results indicate that Indonesia's defense budget has steadily increased over the past decade, contributing to economic growth, particularly in the manufacturing and technology sectors. However, the overall impact on the economy remains mixed due to challenges such as bureaucratic inefficiencies and dependence on imported materials. The discussion highlights the potential for defense R&D investments to generate spillover effects into civilian industries and recommends strategies to enhance the efficiency of defense spending. In conclusion, the implementation of defense economic policies has laid a strong foundation for the development of an independent defense industry in Indonesia. The study suggests that a gradual increase in defense spending, combined with strategic partnerships and innovation, can support both national security and economic stability in the long term